Economic-financial analysis of the use of biscuit bran as an energy alternative in diets for confined lambs - Silva, Luiza de Nazaré Carneiro; Landim, Aline Vieira; Costa, Hélio Henrique Araújo; Vega, Wilder Hernando Ortiz; Costa, Clésio Santos; Araújo, Ricardo Alves; Alencar, Renata Teixeira; Sousa, Luiz Carlos Oliveira de (Semina: Ciências Agrárias, 2021)
The objective of this study was to evaluate the economic and financial viability of replacing corn with biscuit bran (BB) in diets for Morada Nova lambs in feedlot. Twenty lambs confined with initial body weight of 17.00 Â± 3.74 kg were used, arranged in four treatments, diet without biscuit bran (BB) and diets containing 15, 30 or 45% of biscuit bran in place of corn in the diet. Data, expenses and revenues of the activity were obtained during the period of January 2020 in the municipality of Sobral, Ceará. The economic and financial evaluation was carried out descriptively, using ExcelÂ® spreadsheets. In the scenarios evaluated, feeding, animal acquisition and labor costs were the items that most contributed to production costs. The highest food costs were observed in the system that used 15% of BB, representing about 32.86% of the total costs. The simulation for sheep production provided revenue higher than the production costs in all diets tested, resulting in positive economic indicators. On the other hand, although the system that uses diet without biscuit bran provides positive revenue, net income was the lowest (R 12,117.15 year-1). It was observed that all scenarios had a leveling point higher than 5,000 kg of meat year-1. The total productivity of the factors of all treatments evaluated was higher than 1, which indicates that the activity is stable, presenting high internal rates of return. Similarly, profitability rates are attractive, especially for diets containing BB, where the net present value is higher (R 362,143.26). Sensitivity analyses showed that even in the most unfavorable situations, such as a 30% reduction in production and market price, indicators are economically viable. The use of BB does not compromise the economic viability of the diet compared to the diet without BB, they present higher profitability, especially at the level of 15% in the diet.